MENGHUBUNGKAN CSR RATING, KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN - Hidayat, Imam Nur; Maulana, Ilham; Andriani, Nurita (Department of Accounting, Faculty of Economics & Business, 2021)
Abstract : This research revolves around the effect of company performance, CSR rating on company value by using companies listed on the IDX in 2019, the sample was selected using the purposive sampling method, and got a total of 35 companies as the sample used in the test. The variables used in this study include CSR Rating, Return On Assets and Net Profit Margin as indicators of company performance, Tobin's Q and Price to Book Value as indicators of firm value. SEM-PLS was used as a test tool using WarpPLS 7.0. The variables in this study are transformed formatively into latent variables. The result is that the company's performance has a significant positive effect on firm value, the CSR rating has a positive, weakly significance, and the CSR rating can positively moderate the relationship between company performance and firm value.